2022
DOI: 10.3390/polym14040733
|View full text |Cite
|
Sign up to set email alerts
|

Wood Warping Composite by 3D Printing

Abstract: Wood warping is a phenomenon known as a deformation in wood that occurs when changes in moisture content cause an unevenly volumetric change due to fiber orientation. Here we present an investigation of wood warped objects that were fabricated by 3D printing. Similar to natural wood warping, water evaporation causes volume decrease of the printed object, but in contrast, the printing pathway pattern and flow rate dictate the direction of the alignment and its intensity, all of which can be predesigned and affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The dimension of the base unit cells was around 70x65x60 mm in the Z, X, and Y directions, respectively, and the cell size was significantly higher than in this study. Kam et al (2022) concluded that structures (3D wood warped seedpod) can be successful AM by deposition of 1 mm thick layers using water-based inks in the 3D printing application. In this study, successful printing was not achieved for annual ring formation, but success can be obtained by printing models with larger ring diameters, as in previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimension of the base unit cells was around 70x65x60 mm in the Z, X, and Y directions, respectively, and the cell size was significantly higher than in this study. Kam et al (2022) concluded that structures (3D wood warped seedpod) can be successful AM by deposition of 1 mm thick layers using water-based inks in the 3D printing application. In this study, successful printing was not achieved for annual ring formation, but success can be obtained by printing models with larger ring diameters, as in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Additive manufacturing (AM) is an emerging way for printing biomimetic structures. There have been many studies focused on bio-mimicry of wood or wood-related issues, including biomimetics of living wood using AM (Thibaut 2019); wood tissue printing (Markstedt et al 2019); powder-based 3D-printing by binder jetting (BJ) of dry-wood termite frass to bio-mimic the biodegraded wood (Plarre et al 2021); 3D-printed wood warped seedpod by wooden ink with polydisperse wood powder (Kam et al 2022); mechanical properties of printed (stereolithography) composite composed of poplar wood flour modified with methacrylate-based resin (Zhang et al 2021); review data for polylactic acid (PLA) filament modified with plant-sourced materials (Bhagia et al 2021); plant-derived materials used in 3D printing (Sharma et al 2021); biomass-derived 3D printing materials (Ji et al 2020); robotic arms for cellulose-based filament deposition (Iyer and Hasenson 2019); and lignin types and manners of printing of lignin using AM (Ebers et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 266 ] Copyright 2022, MDPI. c) Schematic and images of the multimaterial extrusion‐based DIW printing of a mashrabiya, a chess board model, a nut, screw, and the cross‐section SEM of printed material.…”
Section: Applications Of Printed Lignin‐based Materialsmentioning
confidence: 99%
“…Such objects can also be fabricated by 3D printing. Kam et al [266] developed a printable ink composed of 100% wood-based materials (Figure 16a, wood flour, CNC, and xyloglucan). By carefully controlling the flow rate and printing path, the morphology of the fully dried wooden objects can be tuned from plate to annulus due to the anisotropic shrinkages (Figure 16b), which opens an avenue toward the 4D printing of wood.…”
Section: Engineering Materialsmentioning
confidence: 99%
See 1 more Smart Citation